Upaya Untuk Meningkatkan Hasil Belajar IPA Melalui Metode Pembelajaran Discovery Terbimbing Pada Siswa Kelas V MIN 2 Indragiri Hulu - Aisyah, Siti (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2022)
This study aims to improve science learning outcomes for fifth grade students of MIN 2 Indragiri Hulu using the guided discovery learning method. This type of research is classroom action research. The subjects of this study were students of class V-A MIN 2 Indragiri Hulu who collected 28 students, consisting of 13 male students and 15 female students. The researcher uses the action research model of Kemmis and Taggart. This research was carried out in two cycles of action. In the first cycle, it was conducted in one meeting while in the second cycle it was conducted in two meetings. In each cycle there are planning, implementation, observation, and reflection activities. The instruments used are observation sheets and tests. Before being used in the study, the test was validated empirically and expert judgment. The reliability test was calculated using Cronbach's Alpha. Observational data were analyzed descriptively qualitatively while the test results were analyzed descriptively quantitatively by percentage. The results of the first cycle of research showed that the percentage of students whose scores were above the KKM only reached 71.43%, so they still could not reach the criteria for research success. In cycle II, the steps for applying the discovery learning method to increase student success were done by providing motivation, dividing the number of group members into smaller groups and the heterogeneity of their members, and providing the opportunity to make group presentations on the results of the practicum in front of the class. The percentage of students' scores above the KKM in the second cycle increased to 89.29%. Results Based on the research, it can be seen that the guided discovey method is able to improve science learning outcomes.